PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING CHIPS UNTUK MENINGKATKAN KETERAMPILAN MENULIS PANTUN SISWA KELAS IV SDN 06 KADUR KECAMATAN RUPAT UTARA - Marliza Marliza; Otang Kurniaman; Lazim N Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The research was done because low of ability writing poetry study result of the fourth grade students at SDN 06 Kadur, Rupat Utara subdistrict. KKM stated at school was 70. From 20 students, only 8 students that reached KKM (40,00%), whereas student did not still reach KKM yet were 12 students (60,00%). With score mean of class was 62,53. For solving the problem, there for the researcher implement learning model of talking chips type. The goal of research was for increasing ability writing poetry study result of the fourth grade students at SDN 06 Kadur by implementing learning model of talking chips type. The research was classroom action research. The technique of collecting data by using observation and test. The result of research was collected at first meeting of cycles, the teacher’s activity on classification “enough” (54,17%), after at second meeting, that known the teacher’s activity on classification “good”(70,83%). at first meeting of cycles II, teacher’s activity on classification ” very good”(83,33%), after at second meeting teacher’s activity on classification “very good”(91,66%). At first meeting cycle I, students’ activity on classification “poor”(50,00%), at second meeting students’ activity on classification ”good” (75,00%). At first meeting of cycles II, the students’ activity on classification “good”(79,17%). At second meeting students’ activity on classification“very good”(87,50). At cycles 1 known that total of students reached KKM were 14 students (70,00%) with mean score 77,25. At cycles II, total of students reached KKM were 18 students (90,00%) with mean score 87,25. Based on this research can be concluded that by implementing cooperative learning model of talking chips type can increase ability writing poetry study result of the fourth grade students at SDN 06 Kadur sub-district Rupat Utara.Key word: Cooperative of talking chips type, social studies students achievement